The Numerical Solution of Gas Filtration in Hydrodynamic Interconnected Two-Layer Reservoirs (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This article discusses specific problems of gas filtration in two-layer reservoirs. For the solution, the method of lines with a combination of simple factorization is applied. For the numerical solution of the problem, the Maple software system was used